Identification of Novel Candidate Epitopes on SARS-CoV-2 Proteins for South America: A Review of HLA Frequencies by Country - Requena, David; Médico, Aldhair; Chacón, Ruy D.; Ramírez, Manuel; Marín-Sánchez, Obert (Frontiers in Immunology, 2020)
The Coronavirus disease (COVID-19) is caused by the virus SARS-CoV-2, already responsible for more than 4,3 million confirmed cases and 295,000 deaths worldwide by May 15, 2020. Ongoing efforts to control the pandemic include the development of peptide-based vaccines and diagnostic tests. In these approaches, the HLA allelic diversity plays a crucial role. Despite its importance, current knowledge of HLA allele frequencies in South America is incipient. In this study, we have performed a meta-analysis of datasets reporting HLA frequencies of South American populations, available in scientific literature and/or in the Allele Frequency Net Database. This allowed us to enrich the current scenario in more than 12 million data points. As result, we are presenting updated HLA allelic frequencies per country, including 86 alleles that were previously thought to have frequencies under 5% or unknown. Using the alleles with updated frequency ≥ 5% found in each South American country, we predicted epitopes in SARS-CoV-2 proteins using NetMHCpan (I and II) and MHC flurry. Then, the best predicted epitopes (class-I and -II) were selected based on their match with South American alleles (Coverage Score). Class II predicted epitopes were also filtered based on their three-dimensional exposure. We obtained 14 class-I and 4 class-II candidate epitopes with experimental evidence (reported in the Immune Epitope Database and Analysis Resource), having good coverage scores for South America. Additionally, we are presenting 13 HLA-I and 30 HLA-II novel candidate epitopes without experimental evidence, including 16 class-II candidates in highly-exposed conserved areas of the NTD and RBD regions of the Spike protein. These novel candidates have even better coverage scores for South America than those with experimental evidence. Finally, we show that recent similar studies presenting candidate epitopes also predicted some of our candidates but discarded them in the selection process, resulting in candidates with suboptimal coverage for South America. In conclusion, the candidate epitopes presented provide valuable information for the development of epitope-based strategies against SARS-CoV-2, such as peptide vaccines and diagnostic tests. Additionally, the updated HLA allelic frequencies provide a better representation of South America and may impact different immunogenetic studies.